2021
DOI: 10.1093/hropen/hoab015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adenomyosis on IVF outcomes: a prospective cohort study

Abstract: STUDY QUESTION Does the presence of adenomyosis in women treated with IVF alter IVF outcomes? SUMMARY ANSWER Adenomyosis does not significantly alter IVF outcomes when adjusted for confounding factors including maternal age and smoking status. WHAT IS KNOWN ALREADY Studies evaluating adenomyosis and its impact on infertility, particularly when focusing on IVF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…However, the pregnancy outcomes of the control group were both lower than those in our study, which might be the key reason that led to the different conclusions (LBR 30%, 29.3%, our study 48.1%). Although a recent study reported CRP and LBR in adenomyosis group that were not inferior, the results also showed that FET was related to better pregnancy outcomes compared with fresh ET [20]. In three prior studies, there were no pretreatment CA-125 data available for further comparisons between baseline and changes in the disease severity [8,15,20].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the pregnancy outcomes of the control group were both lower than those in our study, which might be the key reason that led to the different conclusions (LBR 30%, 29.3%, our study 48.1%). Although a recent study reported CRP and LBR in adenomyosis group that were not inferior, the results also showed that FET was related to better pregnancy outcomes compared with fresh ET [20]. In three prior studies, there were no pretreatment CA-125 data available for further comparisons between baseline and changes in the disease severity [8,15,20].…”
Section: Discussionmentioning
confidence: 93%
“…Although a recent study reported CRP and LBR in adenomyosis group that were not inferior, the results also showed that FET was related to better pregnancy outcomes compared with fresh ET [20]. In three prior studies, there were no pretreatment CA-125 data available for further comparisons between baseline and changes in the disease severity [8,15,20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the aforementioned study showed lower pregnancy outcomes in both control and adenomyosis groups compared with our results. In three prior studies 9 , 16 , 22 , there were no pretreatment CA-125 data available for further comparisons between baseline and changes in the disease severity. In our data, there were no differences in first ET, i.e., fresh ET in groups E and C compared with 1st frozen ET in groups A and EA were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that adenomyosis had negative effects to women’s fertility by reducing implantation rate, clinical pregnancy rate, live birth rate and increasing miscarriage rate [ 4 – 6 ]. Moreover, women diagnosed with adenomyosis have more obstetric complications such as premature rupture of membrane, preeclampsia and so on [ 7 ].…”
Section: Introductionmentioning
confidence: 99%